Infrastructure Determinants of Social Vulnerability of the Population - Mariana Bil; Nazariy Popadynets; Tetiana Vlasenko; Yaroslav Landovskyy; Oryslava Hrafska; Iryna Andrushkiv; Nadiya Kubrak (Journal of Vasyl Stefanyk Precarpathian National University)
Improving the research methodology and practice of regulating the social vulnerability of the population requires more attention to infrastructural impacts. Conceptualization of the infrastructural determinants provisions of social vulnerability presupposes a scientific substantiation of the role in creating favourable social conditions and ensuring the resilience of the social system to risks. Infrastructure determinants are an indicator of economic development, a factor in minimizing the vulnerability of the population due to risks, and at the same time, they are a basic condition for creating opportunities for development and self-realization in a modern society of opportunities. When analyzing the impact of infrastructure on the social vulnerability of the population, one should take into account the problematic nature of infrastructure dependence and load. The deepening of interstate divergence in terms of the level of infrastructure development actualizes the priority directions of its development and modernization in the context of reducing the social vulnerability of the population. Initial attention should be given to the critical infrastructure in terms of ensuring the sustainability of the facilities. Information and analytical approaches to the integral assessment of the quality of infrastructure in connection with social processes need to be revised with the introduction of a unified method at the international level. Interstate divergence in infrastructure development has been revealed in the context of competitiveness, social protection, and adaptation potential assessments, which exacerbates inequality in access to infrastructure and social benefits. Six key areas of infrastructure impact regulation have been identified: strategic and managerial, information and analytical, security, modernization, innovation, and protection. It is argued that consideration of infrastructure determinants should form the basis for the unification of methodologies for assessing social vulnerability at the international level. It has been proven that infrastructure can both reduce social vulnerability and exacerbate it in the event of inaccessibility, degradation, or inefficient functioning. The proposed conclusions and classifications form the basis for the development of adaptive social protection strategies for the population in the context of the multifactorial risk-prone nature of the modern world.